2016
DOI: 10.21013/jas.v4.n3.p1
|View full text |Cite
|
Sign up to set email alerts
|

ABCD analysis of Dye-doped Polymers for Photonic Applications

Abstract: Photonics is a subject of scientific study on generating, controlling, harvesting and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…Based on their nonlinear refractive index, the dyes in PMMA-MA matrix behave as good optical limiters even at low powers. These results are quite encouraging for possible applications in nonlinear optical devices [43][44]. The mechanism responsible for optical limiting is mainly attributed to the mechanism of reverse saturation absorption in case of DY-7, which further increased with thermally induced nonlinear refraction.…”
Section: Resultsmentioning
confidence: 56%
“…Based on their nonlinear refractive index, the dyes in PMMA-MA matrix behave as good optical limiters even at low powers. These results are quite encouraging for possible applications in nonlinear optical devices [43][44]. The mechanism responsible for optical limiting is mainly attributed to the mechanism of reverse saturation absorption in case of DY-7, which further increased with thermally induced nonlinear refraction.…”
Section: Resultsmentioning
confidence: 56%
“…It is found that these new indices are effective and simple in the research output of an organization. The detailed analysis of the factors affecting these indices using ABCD analysis framework are [46][47][48][49][50][51][52][53][54][55] is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…(3) ABCD analysis framework [38][39][40][41][42][43][44][45][46][47][48][49] is an effective and integrated method for factor and elemental analysis based on different internal and external issues using four constructs namely advantages, benefits, constructs, and disadvantages. (4) Financial analysis discloses the financial health of the company and hence its sustainability and ability on investment on future expansions.…”
Section: What Are the Analysis Techniques Suitable ?mentioning
confidence: 99%
“…• ABCD Analysis Framework [38][39][40][41][42][43][44][45][46][47][48][49] • Six sigma quality analysis…”
Section: Srinivas Publicationmentioning
confidence: 99%